Polyether-Ether-Ketone applied in Removable Partial Prosthesis Structures: an Integrative Literature Review - Lima, Gabriella Thaís da Silva; Torres Neto, Antônio José; Figueiredo, Viviane Maria Gonçalves de (ARCHIVES OF HEALTH INVESTIGATION, 2025)
The CAD-CAM system is an option to favor the manufacture of Removable Partial Dentures (RPDs). Therefore, the objective was to review the literature in an integrative way regarding the application of Poly-ether-ether-ketone (PEEK) to manufacture structures or components for RPD. The literature search took place between May and June 2022, in Pubmed, BVS, Cochrane Library and Science Direct databases, using search strategies for articles published in any language. The terms of the search strategies were based on descriptors, synonyms, terms present in the title, abstract, Keywords. In all databases, articles were identified that could be included in the research and only 05 articles were included for data extraction and analysis, which are 01 in silico article, 02 in vitro articles and 02 in vivo articles. The review findings identify that studies on the use of PEEK in RPD are scarce. As for the adaptation factor of modified retaining clamps and higher connector accuracy, peek showed satisfactory results in relation to the conventional technique with Co-Cr Alloy structure. In addition, PEEK simulated clamps also exert less tension on the pillars compared to Co-Cr alloy clamps. So, PEEK applied to RPD structures presents itself as a promising material due to its favorable performance in terms of adaptation, precision, stress distribution and patient satisfaction. However, studies with a higher degree of scientific evidence are needed to expand the indication of this material in the daily clinic.